A method for preparing high gelling active material using aluminum ash

By irradiating the phosphoric acid solution with aluminum ash at low temperature plasma and mixing it with gypsum, quicklime, and lightly burned magnesium oxide powder, it forms a highly gelled active material, which solves the problem of ammonia and methane gas release in aluminum ash treatment and realizes aluminum Efficient resource utilization of ash and improved material performance.

CN116282995BActive Publication Date: 2025-01-14CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310141779.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-01-14
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

The existing wet process has problems such as long process chains, many modules, ineffective disposal of hydrogen and methane gas, and incomplete disposal of industrial mixed waste salts in the disposal of aluminum ash and the market acceptance of high aluminum materials prepared. Low.

Method used

After mixing the phosphoric acid solution with aluminum ash, low-temperature plasma irradiation is carried out to produce ammonium-converted phosphorus-aluminum mortar, and then mixed with gypsum, quicklime and lightly burned magnesium oxide powder. Through stirring and curing, a highly gelled active material is formed, which solves the problem of aluminum ash. The problem of water releasing ammonia and methane gases and improves the activity and strength of the material.

Benefits of technology

The rapid resource utilization of aluminum ash is achieved, and the problem of ammonia and methane gas release is solved. The prepared gelled materials are highly active and have a uniaxial compressive strength of up to 56.72MPa, which significantly improves the material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116282995B_ABST
    Figure CN116282995B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-cementing active material using aluminum ash, comprising the following steps: (1) mixing phosphoric acid solution and aluminum ash, stirring, and irradiating with low-temperature plasma to obtain ammonium-converted phosphorus-aluminum mortar; (2) mixing gypsum, quicklime, and light-burned magnesium oxide, stirring evenly, and obtaining high-activity sulfur-calcium-magnesium powder; (3) mixing the ammonium-converted phosphorus-aluminum mortar of step (1) and the high-activity sulfur-calcium-magnesium powder of step (2), stirring, and putting into a mold for curing to obtain a high-cementing active material. The preparation process of the present invention is simple, and the resource utilization of aluminum ash can be quickly realized; in the process of utilizing aluminum ash, the problem of aluminum ash releasing ammonia, methane gas, and hydrogen when it comes into contact with water can be well solved; the cementitious material prepared by the present invention has high activity, and the maximum uniaxial compressive strength of the prepared test block can reach 56.72MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-gelling active material by utilizing aluminum ash, and belongs to the field of harmless disposal and resource utilization of hazardous wastes. Background Art

[0002] In my country, the output of metallic aluminum has increased year by year. A large amount of aluminum ash slag will be produced during the production of metallic aluminum and aluminum smelting. Aluminum ash is listed in the "National List of Hazardous Wastes" (2021 edition) and is reactive and toxic. The aluminum nitride and aluminum carbide contained in the aluminum ash will react when they come into contact with water vapor in the air, and slowly release flammable and explosive gases such as hydrogen, ammonia, and methane. At the same time, the fluoride in the aluminum ash is easily dissolved, causing the fluorine concentration in surface water and soil to exceed the standard, thereby endangering the growth of surrounding plants and animals. According to the content of metallic aluminum, aluminum ash is divided into primary aluminum ash and secondary aluminum ash. Primary aluminum ash has a high content of elemental aluminum and is the primary waste generated in the electrolytic aluminum production process. The primary aluminum ash after the metallic aluminum is recovered is secondary aluminum ash.

[0003] Regarding the disposal and resource utilization of aluminum ash, the current industry tends to treat aluminum ash by wet methods, mixing aluminum ash with water or dilute acid to promote the release of gases such as hydrogen, ammonia, and methane, and then absorbing and discharging the gases, separating the slurry into solid and liquid, pre-treating the separated liquid part, removing impurities, filtering, evaporating and crystallizing to obtain industrial salt, and mixing, stirring, drying, and grinding the separated solid part to produce high-aluminum materials. It can be seen that the current wet process not only has a long process chain and many disposal modules, but also the disposal process cannot properly dispose of or utilize the hydrogen and methane gases generated in the reaction process, and cannot further dispose of the industrial mixed waste salt generated in the evaporation and crystallization process. Moreover, the market acceptance of the prepared high-aluminum materials is also low, and the market sales are unclear. Therefore, based on the problems existing in the existing wet process technology, it is particularly urgent to develop new aluminum ash disposal and resource utilization processes to achieve efficient resource utilization of aluminum ash. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a high cementitious active material using aluminum ash. The preparation process is simple and can quickly realize the resource utilization of aluminum ash. In the process of utilizing aluminum ash, the problem of aluminum ash releasing ammonia, methane gas, hydrogen and the like when it comes into contact with water can be well solved. The prepared cementitious material has high activity, and the maximum uniaxial compressive strength of the prepared test block can reach 56.72MPa.

[0005] Technical solution: To solve the above technical problems, the present invention provides a method for preparing a high gelling active material using aluminum ash, comprising the following steps:

[0006] (1) mixing a phosphoric acid solution and aluminum ash, stirring, and irradiating with low-temperature plasma to obtain an ammonium-converted phosphorus-aluminum ash slurry;

[0007] (2) mixing gypsum, quicklime and lightly burned magnesium oxide, stirring evenly to obtain highly active calcium-sulfur-magnesium powder;

[0008] (3) The ammonium-converted phosphate-aluminum slurry of step (1) and the high-activity calcium-magnesium sulfate powder of step (2) are mixed, stirred, and molded for curing to obtain a high-cementitious material.

[0009] Wherein, the solid-to-liquid ratio of the aluminum ash and the phosphoric acid solution in step (1) is 0.5-1.5:1 mL:g.

[0010] In which, the low-temperature plasma irradiation time in step (1) is 0.5 to 4.5 hours, the low-temperature plasma irradiation voltage is 5 to 75 kV, and the low-temperature plasma action atmosphere is one or more of air, oxygen or ozone.

[0011] Wherein, the mass percentage of phosphoric acid in the phosphoric acid solution in step (1) is 15% to 45%.

[0012] Wherein, the mass ratio of the gypsum, quicklime and light-burned magnesium oxide in step (2) is 1-3:1-3:10.

[0013] Wherein, the mass ratio of the ammonium-converted phosphate-aluminum slurry and the high-activity calcium-magnesium sulfate powder in step (3) is 0.3 to 0.6:1.

[0014] Wherein, the curing time in step (3) is 7 to 21 days.

[0015] Reaction mechanism: After phosphoric acid is mixed with aluminum ash, phosphoric acid reacts with metallic aluminum, aluminum oxide, aluminum nitride, and aluminum carbide in the aluminum ash to generate aluminum phosphate, ammonium dihydrogen phosphate, ammonia, hydrogen, methane gas, etc. During low-temperature plasma irradiation, oxygen free radicals and hydroxyl radicals generated in the low-temperature plasma discharge channel react with ammonium, methane, and hydrogen to generate nitrogen, carbon dioxide, and water. At the same time, oxygen free radicals and hydroxyl radicals generated in the low-temperature plasma discharge channel can also react with aluminum ions, aluminum hydroxide, and aluminum phosphate in the aluminum ash to generate metaaluminate and polyaluminum phosphate and other substances. Ammonium conversion phosphate aluminum mortar and high-activity calcium sulfate magnesium powder are mixed. During the stirring process, ammonium dihydrogen phosphate, metaaluminate, aluminum hydroxide, and polyaluminum phosphate react with calcium oxide, light-burned magnesium oxide, and gypsum, and the magnesium phosphate cement and sulfoaluminate cement react synchronously to generate a specimen with high gelling activity (high strength).

[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The preparation process of the present invention is simple, and the resource utilization of aluminum ash can be quickly realized; 2. In the process of aluminum ash utilization, the problem of aluminum ash releasing ammonia, methane gas, hydrogen and the like when it comes into contact with water can be well solved; 3. The cementitious material prepared by the present invention has high activity, and the maximum uniaxial compressive strength of the prepared test block can reach 56.72MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0019] The main components of aluminum ash: mainly include 65.87% Al2O3, 8.34% Cl, 6.74% Na2O, 5.56% SiO2, 3.72% MgO, 2.46% CaO, 2.24% S, 1.86% TiO2 and other components.

[0020] Light-burned magnesium oxide: Light-burned magnesium oxide is provided by Yingkou Lixin Magnesium Industry Co., Ltd.

[0021] Example 1 Effect of the liquid-to-solid ratio of phosphoric acid solution and aluminum ash on the strength properties of the prepared cementitious material

[0022] According to the liquid-solid ratio of 0.25:1mL:g, 0.3:1mL:g, 0.4:1mL:g, 0.5:1mL:g, 1.0:1mL:g, 1.5:1mL:g, 1.75:1mL:g, 2:1mL:g, 2.25:1mL:g, phosphoric acid solution and aluminum ash are weighed respectively, wherein the concentration of phosphoric acid solution is 15%. The phosphoric acid solution and aluminum ash are mixed, and low-temperature plasma irradiation is performed for 0.5h while stirring to obtain ammonium conversion phosphorus aluminum mortar, wherein the low-temperature plasma (Nanjing Suman Plasma Co., Ltd., CTP-2000K) irradiation voltage is 5kV, and the irradiation atmosphere is air. Gypsum, quicklime, and lightly burned magnesium oxide are weighed respectively according to the mass ratio of 1:1:10, mixed, and stirred evenly to obtain high-activity sulfur calcium magnesium powder. According to the mass ratio of 0.3:1, ammonium conversion phosphorus aluminum mortar and high-activity sulfur calcium magnesium powder are weighed respectively, stirred evenly, put into the mold for curing for 7 days, and a test block with high gelling activity is obtained.

[0023] Strength performance test: The age of the test blocks prepared in this example and the 28-day compressive strength (P 28 The measurement of strength of cement mortar (MPa) is carried out in accordance with the standard GB / T 17671-1999, Test Method for Strength of Cement Mortar (ISO Method).

[0024] Table 1 Effect of liquid-to-solid ratio of phosphoric acid solution and aluminum ash on strength properties of prepared cementitious materials

[0025]

[0026] As shown in Table 1, when the liquid-solid ratio of phosphoric acid solution to aluminum ash is less than 0.5:1 mL:g (the liquid-solid ratio of phosphoric acid solution to aluminum ash = 0.4:1 mL:g, 0.3:1 mL:g, 0.25:1 mL:g and lower ratios not listed in Table 1), the phosphoric acid solution is less, and the dissolution efficiency of aluminum ash is reduced, so that the amount of aluminum phosphate and ammonium dihydrogen phosphate generated during the stirring process is reduced, and the amount of metaaluminate and polyaluminum phosphate generated during the low-temperature plasma irradiation process is reduced, resulting in the performance of the prepared cementitious material being significantly reduced as the liquid-solid ratio of phosphoric acid solution to aluminum ash decreases. When the liquid-solid ratio of phosphoric acid solution to aluminum ash is equal to 0.5-1.5:1 mL:g (the liquid-solid ratio of phosphoric acid solution to aluminum ash = 0.5:1 mL:g, 1:1 mL:g, 1.5:1 mL:g), after phosphoric acid and aluminum ash are mixed, phosphoric acid reacts with metal aluminum, aluminum oxide, aluminum nitride, and aluminum carbide in the aluminum ash to generate aluminum phosphate, ammonium dihydrogen phosphate, ammonia, hydrogen, methane gas, etc. During the low-temperature plasma irradiation process, the oxygen free radicals and hydroxyl free radicals generated in the low-temperature plasma discharge channel react with ammonium, methane, and hydrogen to generate nitrogen, carbon dioxide, and water. At the same time, the oxygen free radicals and hydroxyl free radicals generated in the low-temperature plasma discharge channel can also react with aluminum ions, aluminum hydroxide, and aluminum phosphate in aluminum ash to generate metaaluminate and polyaluminum phosphate and other substances. Finally, the strength of the prepared gel is higher than 45MPa. When the liquid-solid ratio of phosphoric acid solution and aluminum ash is greater than 1.5:1mL:g (liquid-solid ratio of phosphoric acid solution and aluminum ash = 1.75:1mL:g, 2.0:1mL:g, 2.25:1mL:g and lower ratios not listed in Table 2), the amount of phosphoric acid solution is too much, the reaction activity of sulphoaluminate is reduced, and the phosphorus-magnesium phase reaction is too fast, resulting in the performance of the prepared cementitious material being significantly reduced as the liquid-solid ratio of phosphoric acid solution and aluminum ash is further increased. In general, considering the benefits and costs, when the liquid-to-solid ratio of phosphoric acid solution and aluminum ash is equal to 0.5-1.5:1mL:g, it is most conducive to improving the strength properties of the prepared cementitious material.

[0027] Example 2 Effect of the mass ratio of gypsum, quicklime and light-burned magnesium oxide on the strength properties of the prepared cementitious material

[0028] Phosphoric acid solution and aluminum ash were weighed according to a liquid-solid ratio of 1.5:1 mL:g, wherein the concentration of the phosphoric acid solution was 30%. The phosphoric acid solution and aluminum ash were mixed, and low-temperature plasma irradiation was performed for 2.5 hours while stirring to obtain ammonium-converted phosphorus-aluminum ash slurry, wherein the low-temperature plasma (Nanjing Suman Plasma Co., Ltd., CTP-2000K) irradiation voltage was 40 kV, and the irradiation atmosphere was oxygen. According to the mass ratio of 0.5:1:10, 0.6:1:10, 0.8:1:10, 1:0.5:10, 1:0.6:10, 1:0.8:10, 1:1:10, 2:1:10, 3:1:10, 1:2:10, 2:2:10, 3:2:10, 1:3:10, 2:3:10, 3:3:10, 3:3.5:10, 3:4:10, 3:4.5:10, 3.5:3:10, 4:3:10, 4.5:3:10, respectively, and mix and stir evenly to obtain high-activity calcium-sulfur-magnesium powder. According to the mass ratio of 0.45:1, respectively, ammonium-converted phosphate-aluminum mortar and high-activity calcium-sulfur-magnesium powder are weighed, stirred evenly, put into the mold for curing for 14 days, and a test block with high gelling activity is obtained.

[0029] Strength performance test: The age of the specimens prepared by the present invention and the 28-day compressive strength (P 28 The measurement of strength of cement mortar (MPa) is carried out in accordance with the standard GB / T 17671-1999, Test Method for Strength of Cement Mortar (ISO Method).

[0030] Table 2 Effect of mass ratio of gypsum, quicklime and light-burned magnesium oxide on strength properties of prepared cementitious materials

[0031]

[0032]

[0033] It can be seen from Table 2 that when the mass ratio of gypsum, quicklime and light-burned magnesium oxide is less than 1:1:10 (mass ratio of gypsum, quicklime and light-burned magnesium oxide = 1:0.8:10, 1:0.6:10, 1:0.5:10, 0.8:1:10, 0.6:1:10, 0.5:1:10 and lower ratios not listed in Table 2), the amount of gypsum and quicklime is small, and the cementitious reaction is insufficient, resulting in that the performance of the prepared cementitious material decreases significantly with the decrease of the mass ratio of gypsum, quicklime and light-burned magnesium oxide. When the mass ratio of gypsum, quicklime and light-burned magnesium oxide is equal to 1-3:1-3:10 (mass ratio of gypsum, quicklime and light-burned magnesium oxide = 1:1:10, 2:1:10, 3:1:10, 1:2:10, 2:2:10, 3:2:10, 1:3:10, 2:3:10, 3:3:10), the ammonium-converted phosphate-aluminum mortar and the high-activity calcium-magnesium sulfate powder are mixed. During the stirring process, ammonium dihydrogen phosphate, metaaluminate, aluminum hydroxide, and polyaluminum phosphate react with calcium oxide, light-burned magnesium oxide, and gypsum, and simultaneously induce the reaction of magnesium phosphate cement and sulphoaluminate cement to generate specimens with high gelling activity (high strength). Finally, the strength of the prepared gel is higher than 50MPa. When the mass ratio of gypsum, quicklime and light-burned magnesium oxide is greater than 3:3:10 (mass ratio of gypsum, quicklime and light-burned magnesium oxide = 3:3.5:10, 3:4:10, 3:4.5:10, 3.5:3:10, 4:3:10, 4.5:3:10 and higher ratios not listed in Table 2), excessive addition of gypsum and quicklime results in a significant decrease in the performance of the prepared cementitious material as the mass ratio of gypsum, quicklime and light-burned magnesium oxide further increases. In general, in combination with benefits and costs, when the mass ratio of gypsum, quicklime and light-burned magnesium oxide is equal to 1-3:1-3:10, it is most conducive to improving the strength performance of the prepared cementitious material.

[0034] Example 3 Effect of the mass ratio of converted phosphate aluminum mortar and high-activity calcium magnesium sulfate powder on the strength properties of the prepared cementitious material

[0035] According to the liquid-solid ratio of 1.5:1mL:g, phosphoric acid solution and aluminum ash are weighed respectively, wherein the concentration of phosphoric acid solution is 45%. The phosphoric acid solution and aluminum ash are mixed, and low-temperature plasma irradiation is performed for 4.5h while stirring to obtain ammonium-converted phosphorus-aluminum mortar, wherein the low-temperature plasma (Nanjing Suman Plasma Co., Ltd., CTP-2000K) irradiation voltage is 75kV, and the irradiation atmosphere is ozone. Gypsum, quicklime, and light-burned magnesium oxide are weighed respectively according to the mass ratio of 3:3:10, mixed, and stirred evenly to obtain highly active calcium-sulfur-magnesium powder. According to the mass ratio of 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.45:1, 0.6:1, 0.65:1, 0.7:1, and 0.75:1, respectively, ammonium-converted phosphorus-aluminum mortar and highly active calcium-sulfur-magnesium powder are weighed, stirred evenly, and molded for 21 days to obtain a test block with high gelling activity.

[0036] Strength performance test: The age of the specimens prepared by the present invention and the 28-day compressive strength (P 28 The measurement of strength of cement mortar (MPa) is carried out in accordance with the standard GB / T 17671-1999, Test Method for Strength of Cement Mortar (ISO Method).

[0037] Table 3 Effect of the mass ratio of converted phosphate aluminum mortar and high-activity calcium magnesium sulfate powder on the strength properties of the prepared cementitious materials

[0038]

[0039] It can be seen from Table 3 that when the mass ratio of converted phosphate aluminum mortar and high-activity calcium magnesium sulfate powder is less than 0.3:1 (mass ratio of converted phosphate aluminum mortar and high-activity calcium magnesium sulfate powder = 0.25:1, 0.2:1, 0.15:1 and lower ratios not listed in Table 3), the amount of converted phosphate aluminum mortar is small, and the reaction between the converted phosphate aluminum mortar and high-activity calcium magnesium sulfate powder is insufficient, resulting in the performance of the prepared cementitious material being significantly reduced as the mass ratio of converted phosphate aluminum mortar and high-activity calcium magnesium sulfate powder decreases. When the mass ratio of the converted phosphate aluminum mortar and the high-activity calcium sulphate magnesium powder is equal to 0.3-0.6:1 (the mass ratio of the converted phosphate aluminum mortar and the high-activity calcium sulphate magnesium powder = 0.3:1, 0.451, 0.6:1), the ammonium converted phosphate aluminum mortar and the high-activity calcium sulphate magnesium powder are mixed, and during the stirring process, ammonium dihydrogen phosphate, metaaluminate, aluminum hydroxide, polyaluminum phosphate react with calcium oxide, light-burned magnesium oxide, and gypsum, and simultaneously induce the reaction of magnesium phosphate cement and sulphoaluminate cement to generate specimens with high gelling activity (high strength). Finally, the strength of the prepared gel is higher than 52MPa. When the mass ratio of the converted phosphate aluminum mortar and the high-activity calcium sulphate magnesium powder is greater than 0.6:1 (the mass ratio of the converted phosphate aluminum mortar and the high-activity calcium sulphate magnesium powder = 0.65:1, 0.7:1, 0.75:1 and higher ratios not listed in Table 3), the conversion of the phosphate aluminum mortar is excessively added, resulting in the performance of the prepared cementitious material being significantly reduced as the mass ratio of the converted phosphate aluminum mortar and the high-activity calcium sulphate magnesium powder further increases. In general, considering the benefits and costs, when the mass ratio of the converted phosphate aluminum mortar and the high-activity calcium sulphate magnesium powder is equal to 0.3-0.6:1, it is most conducive to improving the strength performance of the prepared cementitious material.

[0040] Comparative example of the effects of different processes on the strength properties of the prepared cementitious materials

[0041] The process of the present invention: weigh phosphoric acid solution and aluminum ash respectively according to the liquid-solid ratio of 1.5:1mL:g, wherein the concentration of the phosphoric acid solution is 45%. Mix the phosphoric acid solution and aluminum ash, and irradiate with low-temperature plasma for 4.5h while stirring to obtain ammonium-converted phosphorus-aluminum mortar, wherein the irradiation voltage of the low-temperature plasma (Nanjing Suman Plasma Co., Ltd., CTP-2000K) is 75kV, and the irradiation atmosphere is ozone. Weigh gypsum, quicklime, and lightly burned magnesium oxide respectively according to the mass ratio of 3:3:10, mix, and stir evenly to obtain highly active sulfur calcium magnesium powder. Weigh ammonium-converted phosphorus-aluminum mortar and highly active sulfur calcium magnesium powder respectively according to the mass ratio of 0.6:1, stir evenly, put into the mold for curing for 21 days, and obtain a test block with high gelling activity.

[0042] Comparative process 1: According to the liquid-solid ratio of 1.5:1mL:g, phosphoric acid solution and aluminum ash are weighed respectively, wherein the concentration of phosphoric acid solution is 45%. The phosphoric acid solution and aluminum ash are mixed and stirred for 4.5h to obtain phosphorus-aluminum mortar. Gypsum, quicklime, and lightly burned magnesium oxide are weighed respectively according to the mass ratio of 3:3:10, mixed, and stirred evenly to obtain highly active calcium-sulfur-magnesium powder. According to the mass ratio of 0.6:1, phosphorus-aluminum mortar and highly active calcium-sulfur-magnesium powder are weighed respectively, stirred evenly, and molded for curing for 21 days to obtain a test block with high gelling activity.

[0043] Comparative process 2: According to the liquid-solid ratio of 1.5:1mL:g, phosphoric acid solution and aluminum ash are weighed respectively, wherein the concentration of phosphoric acid solution is 45%. The phosphoric acid solution and aluminum ash are mixed, and low-temperature plasma irradiation is performed for 4.5h while stirring to obtain ammonium-converted phosphorus-aluminum mortar, wherein the low-temperature plasma (Nanjing Suman Plasma Co., Ltd., CTP-2000K) irradiation voltage is 75kV, and the irradiation atmosphere is ozone. Gypsum and quicklime are weighed respectively according to the mass ratio of 1:1, mixed, and stirred evenly to obtain gypsum ash. According to the mass ratio of 0.6:1, ammonium-converted phosphorus-aluminum mortar and gypsum ash are weighed respectively, stirred evenly, and molded for 21 days to obtain a test block with high gelling activity.

[0044] The strength performance test is the same as that of Example 3. The results of Example are shown in Table 4.

[0045] Table 4 Effect of different processes on the strength properties of prepared cementitious materials

[0046]

[0047] It can be seen from Table 4 that the strength of the test block achieved by the process of the present invention is much higher than that of the comparative process 1 and the comparative process 2, and higher than the sum of the comparative process 1 and the comparative process 2.

Claims

1. A method for preparing a highly gelling active material using aluminum ash, characterized in that: The following steps are involved: (1) mixing a phosphoric acid solution and aluminum ash, stirring, and irradiating with low-temperature plasma to obtain an ammonium-converted phosphorus-aluminum ash slurry; the liquid-to-solid ratio of the phosphoric acid solution to the aluminum ash is 0.5-1.5:1 mL:g; (2) mixing gypsum, quicklime and light-burned magnesium oxide, stirring evenly to obtain highly active calcium-sulfur magnesium powder; the mass ratio of the gypsum, quicklime and light-burned magnesium oxide is 1-3:1-3:10; (3) The ammonium-converted phosphate-aluminum mortar of step (1) and the high-activity calcium-magnesium sulfate powder of step (2) are mixed, stirred, put into a mold for curing, and a high-cementitious material is obtained; the mass ratio of the ammonium-converted phosphate-aluminum mortar to the high-activity calcium-magnesium sulfate powder is 0.3-0.6:

1.

2. The method according to claim 1, characterized in that The low-temperature plasma irradiation time in step (1) is 0.5 to 4.5 hours, the low-temperature plasma irradiation voltage is 5 to 75 kV, and the low-temperature plasma action atmosphere is one or more of air, oxygen or ozone.

3. The method according to claim 1, characterized in that The mass percentage of phosphoric acid in the phosphoric acid solution in step (1) is 15% to 45%.

4. The method according to claim 1, characterized in that: The curing time in step (3) is 7 to 21 days.

Citation Information

Patent Citations

  • Magnesium-based composite cement based on high-activity magnesium oxide powder and preparation method thereof

    CN112279534A

  • Harmless pretreatment and synchronous activation method for aluminum ash

    CN114315182A

  • Method for full-amount resource utilization of secondary aluminum ash

    CN115140719A